1994
DOI: 10.1126/science.266.5183.248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noble Gas Doping in Single-Bubble Sonoluminescence

Abstract: The trillionfold concentration of sound energy by a trapped gas bubble, so as to emit picosecond flashes of ultraviolet light, is found to be extremely sensitive to doping with a noble gas. Increasing the noble gas content of a nitrogen bubble to about 1% dramatically stabilizes the bubble motion and increases the light emission by over an order of magnitude to a value that exceeds the sonoluminescence of either gas alone. The spectrum also strongly depends on the nature of the gas inside the bubble: Xenon yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
151
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 15 publications
6
151
0
2
Order By: Relevance
“…This has also been reported for SBSL from pure water. 3 Interestingly, the He spectrum also shows a broad peak centered at 280 nm. This is very different from He SBSL spectra in pure water in which the continuum shows no peak but instead continues to increase in intensity below 200 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been reported for SBSL from pure water. 3 Interestingly, the He spectrum also shows a broad peak centered at 280 nm. This is very different from He SBSL spectra in pure water in which the continuum shows no peak but instead continues to increase in intensity below 200 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, spectra obtained from water, the fluid used most often for SBSL experiments, consist of featureless broadband emission extending from the near-UV to the near-IR. 3 These continuous spectra have led to predictions of extreme conditions within a single sonoluminescing bubble. Fitting of the featureless spectra to theoretical continuous emission mechanisms such as blackbody and bremsstrahlung emission have led to predictions of visible temperatures being upwards of 10 4 K with core temperatures being much higher.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps most surprisingly, Hiller et al (1994) found a sensitive dependence on the type of gas within the bubble: when the air dissolved in the liquid was replaced with pure nitrogen, the characteristically stable SBSL disappeared. With a gas composed of 80% nitrogen and 20% oxygen, there was still no sonoluminescence.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Hiller et al (1992Hiller et al ( , 1994Hiller et al ( , 1998 measured the spectrum of a sonoluminescing air bubble in water and demonstrated that it increases toward the ultraviolet (Fig. 5).…”
Section: Historical Overviewmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Here, P a is the forcing pressure amplitude and /2 the frequency of the forcing field. This phenomenon is called single bubble sonoluminescence ͑SL͒.…”
Section: Introduction a The Phenomenonmentioning
confidence: 99%